Impact of reclamation activities on the environment case study: reclamation in northern coast of Batam - Priyandes, Alpano (Fakulti Alam Bina, 2009)

(untitled)
This paper presents the findings of a study on the impact of reclamation activities at the northern coast of Batam Island. The study area is at the coastal area of the Sub-District (Kelurahan) of Bengkong Laut, Sadai and Tanjung Buntung. The focus of the study was on the changes in physical-chemical and biological environment as well as on the socioeconomy of fishermen in the form of fishery productivity and income level. Field observation and qualitative descriptive analysis were used as an approach. Data were gathered from government institutions and from a set of questionnaires handed out to a total of 89 respondents. Results showed that reclamation activities changed the environment such as coastal morphology, hydro-oceanography, mangrove and coral reefs deterioration. Other effects are the hill-cutting and tree-cutting of the surrounding area to get filling materials for the reclamation project. Among the consequences observed and recorded were flooding, erosions, sedimentations, and adverse influences on the seawater quality, sea biota, local depletion of several kinds of fishes such as snappers, groupers, and shrimps. These have reduced the income of the fishermen, forcing them to switch to other professions such as becoming tradesmen, laborers, and farmers